Investigating the effect of managers’ shift work and performance prediction on market value of shareholders’ equity in Tehran Stock Exchange - Sadeghi, Navid; Araghi, Maryam Khalili (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
The market value of the shareholders’ equity depends on the implementation of management policies in relation to long-term plans and it will be on the upside if executives focus on implementing these policies. If past events follow a constant process based on prior planning, performance prediction through past events will result. In some cases, the performance of managers is based on increasing their own interests and based on their personal preferences, which causes misleading information about performance prediction to be shared with stakeholders and other beneficiaries. Managers try to predict unrealistic performance in order to increase their management fees by using intermediate and virtual variables which will reduce their professional validity and ultimately lead to a reduction in the market value of the equity. The market value of the shareholders’ equity is directly influenced by the conservative and courageous policies of managers. The purpose of this study is to investigate the effect of managers ’shift work and performance prediction on the market value of shareholders’ equity. This research is a library and analytical-causal study and is based on the analysis of panel data (data panel). In this research, the financial information of 102 companies listed in Tehran Stock Exchange during the period of 2008-2018 (612 companies - the year) has been investigated. The results of the research show that according to the analyzes carried out in relation to the confirmation of the first hypothesis of the research, the style of managers shift working has an adverse and inverse effect on the market value of the shareholders’ equity. Finally, with regard to the analysis made in relation to the confirmation of the second hypothesis of the research, we concluded that performance prediction has a positive and direct effect on the market value of the shareholders’ equity.